2003
DOI: 10.3171/jns.2003.99.2.0287
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of aprotinin in children undergoing craniofacial surgery

Abstract: Aprotinin decreased blood transfusion requirements in pediatric patients undergoing craniofacial reconstruction, thereby reducing the risks associated with exposure to banked blood components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 16 publications
1
37
1
1
Order By: Relevance
“…Our findings are comparable with those of previous trials 19,20,22 in cardiac or scoliosis surgery in children. Neilipovitz et al 19 reported that TXA reduced the volume of PRBCs by 30% compared with a placebo group in children undergoing posterior spinal fusion for scoliosis.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Our findings are comparable with those of previous trials 19,20,22 in cardiac or scoliosis surgery in children. Neilipovitz et al 19 reported that TXA reduced the volume of PRBCs by 30% compared with a placebo group in children undergoing posterior spinal fusion for scoliosis.…”
Section: Discussionsupporting
confidence: 83%
“…23 A few studies 13,16,17,20,23 have shown that intraoperative TXA administration led to less blood loss compared with a placebo group for different types of surgery. Nevertheless, some researchers 19,22 did not report a significant difference in blood loss using TXA or aprotinin, despite a significant decrease in total blood transfusion in the treated patients. In our current study, the amount of intraoperative and total blood loss tended to decrease in patients receiving TXA compared with placebo (51.4 Ϯ 28.3 vs. 61.1 Ϯ 16.8 ml/kg and 64.0 Ϯ 32.4 vs. 76.0 Ϯ 16.1 ml/kg, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Faktör VII preparatının fiyatı ise yüksektir. D'Errico ve arkadaşları 52 aprotininle kraniyal vault operasyonlarında transfüzyon ihtiyacının azaldığını rapor etmişlerdir. Ahmet Z ve arkadaşları 53 çocuklarda (1 ay ve 3 yaş arası) aprotinin uygulamışlar ve kan transfüzyonunu kontrol grubu ile karşılaştırmışlardır.…”
Section: Diğerleriunclassified